One Hand One Plant: Integrating Climate Change Awareness into Education at PGRI Delta University - Lailatul Musyarofah; Muhammad Fadeli; Rahmatiah; Tri Achmad Budi Susilo (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Climate change constitutes one of the most significant global challenges, necessitating immediate action and heightened awareness. In response to this, PGRI Delta University launched the